Factor B and C4b2a Autoantibodies in C3 Glomerulopathy - Hauer, Jill J.; Shao, Dingwu; Zhang, Yuzhou; Nester, Carla M.; Smith, Richard J. H. (Frontiers in Immunology, 2019)
C3 Glomerulopathy (C3G) is a renal disease mediated primarily by dysregulation of the alternative pathway of complement. Complement is the cornerstone of innate immunity. It targets infectious microbes for destruction, clears immune complexes and apoptotic cells from the circulation, and augments the humoral response. In C3G, this process becomes dysregulated, which leads to the deposition of complement proteins—including complement component C3—in the glomerular basement membrane of the kidney. Events that trigger complement are typically environmental insults like infections. Once triggered, in patients who develop C3G, complement activity is sustained by a variety of factors, including rare or novel genetic variants in complement genes and autoantibodies that alter normal complement protein function and/or regulation. Herein, we review two such autoantibodies, one to Factor B and the other to C4b2a, the C3 convertase of the classical and lectin pathways. These two types of autoantibodies are identified in a small fraction of C3G patients and contribute marginally to the C3G phenotype.